PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) - Nadila Andara Putri; A. Sakir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
Abstract: This study aims to see how the influence of profitability and firm size on firm value with capital structure as an intervening vvariabel in consumer goods industrial sector companies listed on the Indonesia Stock Exchange. Profitability is measured by Return On Equity, firm size is measured by Ln total sales, capital structure is measured by comparing Debt To Equity Ratio, and firm value is measured using Tobin's Q. This study uses panel data with a sample of 23 consumer goods industry companies in Indonesia for the 2015-2019 period which was taken using the purposive sampling method and analyzed using the Path Analysis method. The results showed that profitability had a positive and significant effect on firm value, firm size had a positive and insignificant effect on firm value, profitability had a positive and significant effect on capital structure, firm size had a positive and insignificant effect on capital structure, and capital structure was unable to mediate the effect. profitability on firm value, capital structure is not able to mediate the effect of firm size on firm value, capital structure has a negatif and insignificant effect on firm value.